A study on non-fermenting Gram-negative bacilli: their isolation and in vitro susceptibility in a tertiary care hospital in Central India - Preeti Sharma; Varsha Wanjare; Sunanda Shrikhande Zodpey (Microbiologia Medica)
Background: aerobic, non-spore forming Non-Fermenting Gram-Negative Bacilli (NFGNB) are significant nosocomial agents. They can cause infections such as bacteraemia, meningitis, pneumonia, urinary tract infection and osteomyelitis especially in immunocompromised hosts. Identification and monitoring of susceptibility pattern thus become of utmost importance in the management of these Multidrug Resistant (MDR) pathogens.